Hadzinia ferrani, sp. n. (Opiliones: Nemastomatidae), a highly specialized troglobiotic harvestman from Slovenia - Novak, Tone; Kozel, Peter (Zootaxa, 2014)
A highly specialized, endemic troglobiotic harvestman, Hadzinia ferrani sp. n., recently found in the Ferranova buža cave in the karst of Mt. Ulovka in central Slovenia is described. It is characterized by its small, 1.1−1.4 mm long body and very long, thin appendages, with leg II more than 20-times as long as the body. Although very similar to Nemaspela Šilhavý, 1966, the genus Hadzinia Šilhavý, 1966 can be clearly differentiated from Nemaspela by its truncated glans and short stylus, well delimited from the glans. According to these characteristics, Hadzinia is assumed most closely related to Pyza Staręga, 1976 and Vestiferum Martens, 2006 rather than to Nemaspela with the glans gradually tapering into a mostly long stylus. Genital morphology is the most appropriate and probably the only morphological approach for investigating relationships among the taxa under study.